What determines the choice of language with friends and neighbors? the case of Malaysian university undergraduates. - Md. Mostafizar Rahman, Abu Rashed; Chan, Swee Heng; Abdullah, Ain Nadzimah (Language in India, 2008)
Bi-/multilingual people exercise choices of language among the languages of their linguistic repertoire for different purposes in different domains. The choice is determined by various factors such as ethnicity, proficiency, attitudes, socio-cultural background, language policy, and in particular, the domain itself.Malaysia being a multilingual country, what languages are chosen with friends and relatives, and what determines the choice constitute the main objectives of this paper.Data for this paper was collected through a questionnaire survey administered to a sample of university undergraduates and analyzed those using SPSS. The findings show that respondents from the major ethnic groups preferred their respective ethnic languages with friends and neighbours of the same ethnic backgrounds but choice of Bahasa Malaysia (BM) among the non-Malays and choice for English among respondents irrespective of ethnicity increase while the interlocutors belong to other ethnic backgrounds. Ethnicity, proficiency and domain of use were found to be contributing factors of language choice with friends and neighbours in Malaysia.